Modeling analysis of meniscus of knee joint during soccer kicking - Mohd Firdaus, Mohd Jaafar (2013)
The meniscus is important in many aspects of knee function. The placement of meniscus where been located between the two bones of femur and tibia gives an advantage towards the knee joint. It is when the load been transmitted across the joint in order to give maximal congruency towards the joint. This study will focuses on two objectives which are to observe the effects towards the knee joint which having various cases of meniscus and also to observe the functionality of the meniscus which is wedges in shape. The method used in this study is a simulation of knee joint which is consisting of three main parts, femur, tibia and meniscus. In order to observe what the effects towards the knee joint, various cases is being simulated which are knee joint with healthy meniscus compared with knee joint with various of torn meniscus and a simulation of full leg with and without knee pad with existence of external impact. The boundary condition of force parameter is calculated from the ball velocity after being kicked where the comparison between the two types of kicking result with instep kicking got high impact force and distributed force than inside kicking. The highest distributed force then is used for the simulation. Simulation result shows that a healthy meniscus transmits load across the joint in a uniform state within the range of 0.3 MPa and 0.4MPa. For torn meniscus, the result shows that it is failed to transmit the load across the joint. Thus an excessive stress is recorded across the surface of the tibia. The highest stress recorded is 0.5 MPa. For second simulation, 1000 N is used as an external force exerted to the leg surface. Result shows that the external force applied on the surface of the leg will give an effect towards the internal part of the knee joint where causing the knee joint to bend and meniscus to be compressed. Comparison between the full leg with and without knee pad shows that full leg without knee pad is having large of knee joint bending and meniscus be compressed more than full leg with knee pad. From these to simulation, an observation can be made where the placement of the meniscus between the femur and tibia is to maintain the congruency between the bones and to prevent an excessive stress happen to the joint.